Perancangan dan analisis sistem instalasi hidran untuk mencegah bahaya kebakaran pada gedung workshop di BP3 Curug - Sakroni, Muchammad Imam; Ali Rosyidin (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2024)
The Workshop Building at BP3 Curug is located more than 50 M from the nearest hydrant point. Based on SNI-03-1735-2000, every part of the fire engine access route on building land must be within a distance of 50 M from city hydrants. If city hydrants are not available, yard hydrants must be provided. Seeing these conditions, the Workshop Building must have a fire protection system. The aim of the research is how to design hydrant installations and determine the number and layout of yard hydrants needed in the Workshop Building. In collecting data, the research methodology used was observation and interview methods. The results of the calculation and design of the amount of water supply needed for 30 minutes, namely 72 M3 with an available reservoir of 96 M3 so that it is sufficient to supply the planned system. The total pump head obtained was 107.8 M with the pump power required by the system design being 42 KW. However, the available pumps are insufficient to meet needs. The number and layout of yard hydrants required is 1 (one) with the lane distance between FHP 5 and FHP 6 in exceptional conditions (SNI-03-1735-2000) may be more than 50 M, namely 69 M and the distance between yard hydrants and the walls of the Workshop Building are 12 M (NFPA 1).